PERAN TAX CENTER : PERSPEKTIF INTERNAL DAN EKSTERNAL (STUDI PADA TAX CENTER FEB UNIVERSITAS LANCANG KUNING) - Salmiah, Neneng; Zaharman, Zaharman; Novianti, Serly (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This research was conducted at the Tax Center Unit of the Faculty of Economics and Business, Lancang Kuning University (Unilak) as one of the tax centers in Riau Province. This research aims to analyze the role of the FEB Unilak Tax Center both from an internal perspective (tax volunteers) and from an external perspective (taxpayers and KPP Pratama Pekanbaru Senapelan). The problem formulation is how the role of the FEB Unilak Tax Center is, both from an internal and external perspective. The research object is the role of the FEB Unulak Tax Center. The data source is primary data in the form of interviews with informants, namely FEB Unilak graduates who have been tax volunteers, individual taxpayer who report SPT Tahunan OP at the FEB Unilak Tax Center, and KPP Pratama Pekanbaru Senapelan employees. Data collection techniques are observation, interviews and documentation. The data analysis technique using qualitative descriptive consists of three stages, namely data reduction, data presentation and drawing conclusions. From the research results, it was concluded that the role of the tax center from an internal perspective (tax volunteers) is to increase student competency and graduate competitiveness so that it is very helpful in entering the world of work in the fields of accounting, taxation and helping success in the world of work. The role of the FEB Unilak Tax Center from an external perspective, in this case KPP Pratama Pekanbaru Senapelan, is to increase compliance of SPT Tahunan OP Reporting even though it is not yet optimal. The role of the FEB Unilak Tax Center from an external perspective, in this case individual taxpayer is to really help individual taxpayer in report SPT Tahunan OP and with very good service.